PENERAPAN MEDIA WAREK (WAYANG KARAKTER) UNTUK MENUMBUHKAN NILAI RELIGIUS PADA PEMBELAJARAN MENYIMAK SISWA KELAS 1 SEKOLAH DASAR - Cerianing Putri Pratiwi (MUADDIB Jurnal Kependidikan dan Keislaman, 2018)
The purpose of this study is to know the application of wayang media characters to grow religious values on learning listening to grade 1 students of SDN Plangkrongan 3. Type of this research is descriptive qualitative research. The data in this research are verbal data and nonverbal data. Verbal data that is the recording of the application of wayang characters media to cultivate religious values on learning listening to grade 1 students of SDN Plangkrongan 3. Nonverbal data is the evaluation of listening ability. In this research, the subjects are the first grade teachers of SDN Plangkrongan 3 and the 1st grade students of SDN Plangkrongan 3. Data collection techniques in this research are (a) observation, (b) interview, and (c) test, (d) documentation. In this research data analysis techniques using interactive data analysis, there are three steps: data reduction, data presentation, and conclusion. Implementation of wayang characters media to cultivate religious values on learning listening to grade 1 students of SDN Plangkrongan 3 is already running in accordance with the plan and learning objectives have been achieved. From the results of the evaluation listening given, the results of listening to students is good enough. The average grade of grade V SDN Plangkrongan 3 is 85.6% of the total students 9. All students have been able to answer questions from the fairy tales that have been heard.